Pengaruh Country of Origin, Citra Merek, dan Worldmindedness Terhadap Keputusan Pembelian Produk KFC di Kabupaten Jember (Jurnal Strategi dan Bisnis, 2022)
This study aims to determine the effect of Country of Origin, Brand Image, and Worldmindedness on the Purchase Decision of KFC Products in Jember Regency. This type of research is quantitative. Primary data from this study was obtained directly through the distribution of questionnaires distributed to respondents who had made purchases at KFC Jember. The population in this study are consumers of KFC Jember products whose numbers are not known for certain because the number is not limited. The number of samples in this study were 104 respondents who were selected using accidental sampling. The results of this study indicate that the coefficient value of the Country of Origin variable is a positive value of 0.210. Additionally, the brand image variable's coefficient value is positive 0.222. Whereasthe coefficient value of the Worldmindness variable is positive 0.543. These three variables proved to have a significant effect on purchasing decisions at KFC Jember. Keywords: Country of Origin; Brand Image; Worldmindedness; Purcashe Decision